SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN PERUMAHAN DI BANDAR LAMPUNG - Hilda Dwi Yunita; Fatimah Fahurian (Explore: Jurnal Sistem Informasi dan Telematika (Telekomunikasi, Multimedia dan Informatika), 2019)
Houses are one of the basic human needs besides clothing and food. There are many factors that influence everyone to choose a house to live in, including a house model, house prices, land area, building area, distance to location, environment and so on. In Bandar Lampung, there are many housing estates. But the absence of a system that can be used by the community as prospective buyers to choose housing to be purchased in accordance with the desired criteria.  This has resulted in consumers, especially buyers of houses or housing, still finding it difficult to find housing according to their desired and financial needs. In this study a housing decision support system was applied. And the results of decision support systems can help decision makers, namely buyers in choosing housing that fits the desired criteria and according to needs and finances.